2017
DOI: 10.24856/mem.v32i2.538
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Ekuitas Merek Dan Promosi Penjualan Terhadap Loyalitas Pelanggan Dimediasi Keputusan Pembelian

Abstract: AbstrakPenelitian ini bertujuan tentang pengaruh ekuitas merek dan promosi penjualan terhadap loyalitas pelanggan di mediasi keputusan pembelian pada pengguna operator seluler Telkomsel di kalangan mahasiswa UTA'45 Jakarta. Metode pengambilan sampel dengan teknik non-probability sampling sebanyak 220 orang. Metode analisis data menggunakan Structural Equation Modeling-Partial Least Square (SEM-PLS) dengan menggunakan software Smart PLS versi 3. Tahapan perhitungan PLS menggunakan 2 model yaitu Pengukuran Model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 3 publications
2
3
0
10
Order By: Relevance
“…In the ninth Hypothesis Test (H9), it was found that the results of data analysis supported the ninth hypothesis, namely that the decision to release private label products would increase customer turnover. This is supported by previous research that shows that the purchase fee has an influence on customer loyalty (Diansyah & Putera, 2017). (Sulistiani, 2017) also showed the results of research that purchasing decisions on customer loyalty have a positive and significant influence.…”
Section: Mardiana Nuryakinsupporting
confidence: 82%
“…In the ninth Hypothesis Test (H9), it was found that the results of data analysis supported the ninth hypothesis, namely that the decision to release private label products would increase customer turnover. This is supported by previous research that shows that the purchase fee has an influence on customer loyalty (Diansyah & Putera, 2017). (Sulistiani, 2017) also showed the results of research that purchasing decisions on customer loyalty have a positive and significant influence.…”
Section: Mardiana Nuryakinsupporting
confidence: 82%
“…If consumers have a good perception of the brand, it will affect the formation of product choices to be purchased, which in turn will form a positive attitude which in turn will influence purchasing decisions. [10], [11]. This is in line with the opinion of Sodik (2004) that the information obtained and processed by consumers will form a person's preference for an object.…”
Section: Introductionsupporting
confidence: 81%
“…A previous study showed a positive relation between purchase decisions and loyalty (Hatta & Setiarini, 2018). A previous study showed an indirect influence of CRM on loyalty through purchase decisions (Diansyah & Putera, 2017;Kusumandayu, 2016). CRM is considered a technology related to data, which allows higher profits or a strategic approach that gives value (Triznova et al, 2015).…”
Section: Decision To Stay On Loyaltymentioning
confidence: 92%
“…It is better to retain old customers who make repeat purchases and recommend them to others than to find new customers. Previous research has shown a relationship between staying decisions and customer loyalty (Diansyah & Putera, 2017).…”
Section: Research Backgroundmentioning
confidence: 98%